Review Jurnal : Perbandingan Uji Stabilitas Paracetamol dan Asetosal dalam Sediaan Tablet - Rakha Widyastama; Sri Tami Dewi; Nor Latifah (Lembaga Pengembangan Kinerja Dosen, 2025)
Drug stability testing is a critical aspect in the development and storage of pharmaceutical preparations to ensure the safety, quality, and efficacy of the product throughout its shelf life. Drug stability is influenced by various intrinsic and extrinsic factors, such as temperature, humidity, light, pH, and chemical and physical interactions. Stability evaluation includes long-term stability testing, accelerated stability, and in-use stability testing in accordance with ICH, WHO, or FDA guidelines. Parameters assessed include the potency of the active substance, degradant levels, physicochemical properties, and microbiological characteristics. The results of stability studies are used to determine shelf life, storage recommendations, and appropriate packaging. A thorough understanding of drug stability is essential in the pharmaceutical industry to ensure regulatory compliance and protect patient health.